Enhanced network recovery scheme on real-time switched ethernet for naval combat system. (25th February 2015) - Wei, Yang; Kim, Dong-Seong
This paper proposes an enhanced network recovery (ENR) scheme based on switched ethernet to handle network failures in the naval combat system. In this study, network failure recovery is explained through message scheduling on switched ethernet, which is based on previous works on flexible time trigger (FTT) ethernet. The proposed ENR method expands the previous works by including a revised spanning tree construction scheme and efficient failure detection scheme on real-time switched ethernet for system robustness. To show the advantages of the ENR scheme, the performance of the proposed method is compared with the performance of the existing protocol called time-triggered ethernet (TTEthernet). The simulation results show that the proposed ENR scheme outperforms the TTEthernet in terms of the end to end delay and message delivery probability.